Identification of common cardiometabolic alterations and deregulated pathways in mouse and pig models of aging. Issue 9 (30th July 2020) - Fanjul, Víctor; Jorge, Inmaculada; Camafeita, Emilio; Macías, Álvaro; González‐Gómez, Cristina; Barettino, Ana; Dorado, Beatriz; Andrés‐Manzano, María Jesús; Rivera‐Torres, José; Vázquez, Jesús; López‐Otín, Carlos; Andrés, Vicente
Abstract: Aging is the main risk factor for cardiovascular and metabolic diseases, which have become a global concern as the world population ages. These diseases and the aging process are exacerbated in Hutchinson–Gilford progeria syndrome (HGPS or progeria). Here, we evaluated the cardiometabolic disease in animal models of premature and normal aging with the aim of identifying alterations that are shared or specific to each condition. Despite differences in body composition and metabolic markers, prematurely and normally aging mice developed heart failure and similar cardiac electrical abnormalities. High‐throughput proteomics of the hearts of progeric and normally aged mice revealed altered protein oxidation and glycation, as well as dysregulated pathways regulating energy metabolism, proteostasis, gene expression, and cardiac muscle contraction. These results were corroborated in the hearts of progeric pigs, underscoring the translational potential of our findings, which could help in the design of strategies to prevent or slow age‐related cardiometabolic disease. Abstract : We have evaluated cardiac and metabolic disease in animal models of aging. Despite differences in body composition, progeric and normally aged mice developed heart failure and similar cardiac electrical alterations. High‐throughput proteomics of the hearts of these animals revealed dysregulation of energy metabolism, proteostasis, gene expression, and cardiac contraction pathways. These results were corroborated in progeric pigs, underscoring the translational potential of our findings.